Key principles and characteristics of an Islamic brand model with special reference to Islamic brand attire - Muhammad Saiful Islam, Ismail (2018)
Back in 2007, Islamic brands captivated the attention of marketing scholars. Most previous studies regarding Islamic brands adapted the conventional brand theories and models in examining Muslim consumers' behaviour towards a brand. The adaptation of the conventional brand theory is inappropriate to explain from the Islamic point of view. Based on the call for the development of an Islamic brand, this study aimed to develop the Islamic brand model from the Islamic perspectives specifically in Islamic attire. Hence, the four objectives of this study were to: (a) explore the meaning of lslamic brand, (b) explore the characteristics of the Islamic brand, (c) identify the characteristics of the Islamic principles in shaping the Islamic brand attire, and (d) investigate firms' current practice in the Islamic brand attire industry. A qualitative approach was employed to gather information for the study through: (a) literature review, (b) interviews [thirty four (34) Islamic experts and thirteen (13) firms], and (c) the observation method. The data analysis used the thematic analysis by applying the method of istidlal. The results demonstrate that: (a) the definition oflslamic brand should consist of three principals; aqidah, sharia, and akhlak, (b) there are three main characteristics in the Islamic brand, i.e. aqidah, sharia, and akhlak, (c) there are relationships between aqidah, sharia, and akhlak in shaping the Islamic brand, and (d) only a few firms comply with the Islamic brand core principles while the others are still based on the conventional brand value and aspiration. This research complements the conceptual contribution (new knowledge of definition, characteristics, and interaction between Islamic core principles and Islamic brand attire) and the methodological contribution (epistemology and ontology from the Islamic perspective, and applying the method of istidlal in the thematic data analysis). Lastly, the findings can be used by Muslim and non-Muslim firms in designing the product.